Is there a relationship between the number of lymph nodes and disease parameters in patients who underwent retropubic prostatectomy - (:unkn) unknown (SPRINGER, 2014)
We aimed to establish the relationship between lymph nodes (LNs) counts that were removed with standard pelvic lymph node dissection (sPLND) and different disease parameters in patients who underwent radical prostatectomy (RP). A total of 70 patients who underwent sPLND during RP were scanned retrospectively. The scanned parameters were levels of serum PSA, the total weight of the removed prostate, the amount as a percentage of the tumor in the prostate tissue, the stage of the tumor, the total Gleason score (GS) and the number of standard pelvic lymph nodes that were removed from both right and left sides. The average age of the patients was 59 years. A positive correlation was found between the total GS and the number of lymph nodes; while this correlation was significant (p = 0.0038), there was no significant difference between lymph nodes counts and other scanned parameters. The average pelvic lymph node numbers of patients with GS of 6-7 and 8 were 10.4-11.5 and 13.2, respectively. Lymph nodes metastases were found in 3 (4.2 %) patients whose average pelvic lymph node number was 17.3. The chance of cure or decreased recurrence is much more possible in patients who had received extended PLND or at least standard one, because of the removal of much more lymph node tissues that have a high probability of disseminating cancer cells. This position can especially be considered in patients with high GS.
Keywords: Lymph nodes; Metastasis; Disease parameters; Prostate cancer; EXTENDED PELVIC LYMPHADENECTOMY; RADICAL PROSTATECTOMY; NODAL METASTASIS; POSITIVE NODES; CANCER; DISSECTION; MEN; PROBABILITY; PROGRESSION; EXPERIENCE